HUBUNGAN PERSEPSI SISWA TENTANG KOMPETENSI GURU DENGAN HASIL BELAJAR SISWA KELAS XI IPS MATA PELAJARAN EKONOMI DI SMAN 2 KOTA JAMBI - Fachruddiansyah Muslim (LPPM Universitas Jambi, 2017)
In a teaching learning process, students are expected to have high interest and enthusiasm in the classroom. Teachers who have the competencies would be able to create conditions for effective learning, fun and effective classroom management. Student perceptions of teachers in the learning process would indirectly mean that the student has had interest in these subjects. Through the perpection that teachers are teaching students to have a solid competence as a teacher and a professional will be able to evoke the spirit of learning that impact student learning outcomes in both. The purpose of this study was to determine how students perceptions of competence and its relationship to students learning outcomes.Subjects in this study are students – a class XI IPS students at SMA Negeri 2 Jambi City which is used as a sample of 50 students. In the process of data collection, carried out a total spread of 31 items questionnaire wich questions that are relevant indicators of what the objectives of this study. Then after it’s collected questionnaires analyzed by using the formula categories and the categories that have been determined. And to determine its relationship with the goal should learn, questionnaires analyzed by manual and by using the SPSS 16.0 computer applications.From the research found that student perceptions of teacher competence is highest percentage of students percepstions about the competence of the teacher’s personality which amounted to 83,5 % and categorized very well. As for the indicator of student perceptions about of competence of another teacher for : students percepstions about the competence of the teacher’s pedagogic (73,76%) students percepstions about the competence of the teacher’s professional (83%) and students percepstions about the competence of the teacher’s social (78,2%). Next, coefficient of relationship students percepstions about the competence of the teacher’s with a favorable economic study results obtained rxy = 0,511. Therefore we can conclude that there is a relationship between variables X and variables Y and is included in the interpretation.